2015
DOI: 10.1136/bcr-2015-212483
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent pericardial effusion and tamponade in a patient with Erdheim-Chester disease (ECD)

Abstract: Erdheim-Chester disease (ECD) is a rare xanthogranulomatous disorder characterised by the proliferation of lipid laden histiocytes along with infiltration of various organs of the body. Although commonly presenting with bone pains secondary to bony infiltration, cardiac involvement in the form of periaortic fibrosis and pericardial involvement may be seen in a subgroup of patients. We report a case of ECD presenting as recurrent pericardial effusion along with pericardial tamponade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…The latter can be seen in the form of pericarditis, asymptomatic pericardial effusion to life-threatening, rapid, recurrent pericardial tamponade. Recurrent pericardial effusions with tamponade caused by ECD, however, are extremely rare [7]. Mishra et al reported a patient who continued to experience clinical deterioration despite multiple pericardiocentesis and pericardial window [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter can be seen in the form of pericarditis, asymptomatic pericardial effusion to life-threatening, rapid, recurrent pericardial tamponade. Recurrent pericardial effusions with tamponade caused by ECD, however, are extremely rare [7]. Mishra et al reported a patient who continued to experience clinical deterioration despite multiple pericardiocentesis and pericardial window [7].…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent pericardial effusions with tamponade caused by ECD, however, are extremely rare [7]. Mishra et al reported a patient who continued to experience clinical deterioration despite multiple pericardiocentesis and pericardial window [7]. Only two cases of ECD with constrictive pericarditis have been reported in the literature [8, 9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, in all cases of symptomatic pericardial effusion due to ECD described in the medical literature, a first-line pharmacological approach with IFN-α has proven ineffective. In some cases, a surgical procedure such as pleural–pericardial window or pericardiectomy was needed; other patients developed cardiac tamponade despite IFN-α treatment and did not survive ( 25 , 26 ). The pericardial fluid from ECD patients with pericardial involvement is highly inflammatory, with increased levels of pro-inflammatory cytokines ( 14 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…The traditional drug of choice in ECD is IFN-α ( 7 ). However, we preferred not to choose IFN-α, as previous experience suggests limited efficacy in cases of severe heart inflammation ( 25 , 26 ). As a valid alternative, we focused on vemurafenib, a small molecule inhibitor of BRAFV600E, which is highly effective in the treatment of ECD ( 27 ).…”
Section: Case Reportmentioning
confidence: 99%